SOCIAL NETWORKS IN THE BOARDROOM. Issue 4 (24th July 2013) - Kramarz, Francis; Thesmar, David
Abstract This paper provides evidence that social networks strongly affect board composition and are detrimental to corporate governance. Our empirical investigation relies on a large data set of executives and outside directors of French public firms. This data source is a matched employer–employee data set that provides detailed information on directors/CEOs as well as information about the firm employing them. We find a strong and robust correlation between the CEO's network and that of his directors. Networks of former high‐ranking civil servants are the most active in shaping board composition. Our identification strategy takes into account not only firm and directors' fixed effects but also the matching of firms and director in terms of one observable and one unobservable characteristic. Turning to the direct effects of such network activity, we find that firms in which these networks are most active pay their CEOs more, are less likely to replace a CEO who underperforms, and engage in less value‐creating acquisitions. These findings suggest that social networks are active in the boardroom and have detrimental effects on firms' governance.